Metal‐Based Nanoparticles: Shedding Light on Metal‐Based Nanoparticles in Zebrafish by Computed Tomography with Micrometer Resolution (Small 31/2020). Issue 31 (6th August 2020) - Cörek, Emre; Rodgers, Griffin; Siegrist, Stefan; Einfalt, Tomaz; Detampel, Pascal; Schlepütz, Christian M.; Sieber, Sandro; Fluder, Pascal; Schulz, Georg; Unterweger, Harald; Alexiou, Christoph; Müller, Bert; et al.
Abstract : Superparamagnetic iron oxide nanoparticles (SPIONs) are clinically used as diagnostic agents, serving as a contrast media when exposed to a magnetic field. In article number 2000746, Jörg Huwyler and co‐workers evaluate synchrotron radiation‐based hard X‐ray tomography (SRμCT) for the localization of SPIONs in soft tissues. In the cover, the tissue distribution of SPIONs is visualized after intravenous injection in a three‐day old zebrafish embryo by SRμCT, with views within the blood vessel looking at the surrounding soft tissue and onto SPIONs engulfed by macrophages. Image: Courtesy of Jan Stephan Bolten.